Identify Students’ Critical Thinking Skills During Chemistry Learning Process of Molecular Shapes - Dijaya, Arisna Oktavia; Hendayana, Sumar; Supriatna, Asep (FKIP-Universitas Riau, 2020)
Critical thinking skills become essential skills for students demanded by the 2013 curriculum. Effective learning critical thinking is very important for students in the classroom. This study aimed to identify students' critical thinking skills during chemistry learning process of molecular shapes. The method applied in this study was descriptive qualitative with a case study approach. It was conducted at one of high schools in Bandung were the participants were the tenth grade students’. The instruments used for data collection were audio, video and observation sheets. The collected data were analyzed using Transcript Based Lesson Analysis (TBLA). The results indicated that four out of twelve indicators of critical thinking skill had been identified in learning molecular shapes. The four indicators are formulating questions, answering the “why” questions, focusing on a question, judging the credibility of the sources, and interacting with others. The low achievement of critical thinking indicators was due to the method used in teaching which is still informative or transferring knowledge from teacher to student (teacher-centered) without giving sufficient time for students to reflect the material presented, link it with prior knowledge, or apply it in real life situations.